Production of Co Doped Na0.67Mn0.5Fe0.43Ti0.07O2 Cathode Materials and Examination of Electrochemical Properties - Toy, Ömer Faruk; Buldu, Murat; Altın, Serdar; Canbay, Canan Aksu (Fırat Üniversitesi, 2025)
In this study, the production of compound ??Na?_0.67 (Mn?_(0.5-x) ?Co?_x ?Fe?_0.43 ?Ti?_0.07)O_2 was carried out according to the traditional solid-state reaction method by adding Co element at the ratio of x = 0.1, 0.2, 0.3, 0.4 and 0.5. Structural analysis of the produced samples were performed by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray (EDX) analyses, respectively. The prepared powder materials were used in the production of cathode active materials in Na-ion batteries and button type CR2032 cells were produced and battery properties were examined. The performances of the batteries were investigated by performing electrochemical analyzes with the produced battery cells. Within the scope of this study, Cyclic Voltammetry (CV), Impedance Spectroscopy (EIS) and cycle performance measurements were taken for half-cell tests using Na metal. When the battery test results were evaluated, it was determined that the electrochemical properties changed significantly with Co doping, and capacity losses were less in samples with x = 0.2 doping.

Bu çalışmada ??Na?_0,67 (Mn?_(0,5-x) ?Co?_x ?Fe?_0,43 ?Ti?_0,07)O_2 bileşiğinin üretimleri x=0,1, 0,2, 0,3, 0,4 ve 0,5 oranında Co elementi katkılanarak geleneksel katıhal reaksiyon yöntemine göre gerçekleştirilmiştir. Üretilen örneklerin yapısal analizleri sırasıyla X-ışını kırınımı (XRD), Fourier Dönüşümlü Kızılötesi Spektroskopisi (FTIR), Taramalı Elektron Mikroskobu (SEM) ve Enerji Dağılımlı X-Işını (EDX) yöntemleri ile gerçekleştirilmiştir. Hazırlanan toz malzemeler Na-iyon bataryalarda katot aktif malzemelerinin üretiminde kullanılmış ve buton tipi CR2032 hücreler üretilerek elektrokimyasal özellikleri incelenmiştir. Bu Çalışma kapsamında Na metali kullanılarak yarım hücre testleri için Döngüsel Voltametri (CV), Empedans Spektroskopisi (EİS), çevrim performans ölçümleri alınmıştır. Elde edilen batarya test sonuçları değerlendirildiğinde Co katkılanması ile birlikte elektrokimyasal özelliklerin ciddi bir şekilde değiştiği ve x=0,2 katkılı örneklerde kapasite kayıplarının %16,7 değeri ile diğerlerine göre daha az olduğu belirlenmiştir.
Co Katkılı Na0,67Mn0,5Fe0,43Ti0,07O2 Katot Malzemelerinin Üretimi ve Elektrokimyasal Özelliklerinin İncelenmesi
Keywords: General Physics; Genel Fizik